Performance evaluation of broken gap Esaki tunnel diodes on Si and GaSb substrates. Issue 1 (1st January 2016) - Thomas, P.M.; Filmer, M.J.; Gaur, A.; Rommel, S.L.; Bhatnagar, K.; Droopad, R.
Abstract : n ‐InAs/ p ‐GaSb Esaki diodes with 3 nm GaSb i ‐layers are fabricated on Si and GaSb substrates. The on Si sample devices exhibit lower peak to valley ratios and peak current density than their on GaSb counterparts at 3.27 against 4.45 and 119 against 336 kA/cm 2, respectively. The findings are similar to other reports of integrating III–V Esaki diodes onto Si.